Stars and Ribbons : Winter Wassailing in Wales. - Ifans, Rhiannon (University of Wales Press, 2022)
This book provides Welsh wassailing songs in their original language, translated into English and with musical notation, together with a vivid introduction to their significance within the society in which they were sung.
Description based upon print version of record.
Keywords: Folk songs, Welsh -- History and criticism.; Folk music -- Wales -- History and criticism.; Chansons folkloriques galloises -- Histoire et critique.; Folk music; Folk songs, Welsh; Wales; Criticism, interpretation, etc.